A CONSERVED MRF4 PROMOTER DRIVES TRANSGENIC EXPRESSION IN XENOPUS EMBRYONIC SOMITES AND ADULT MUSCLE - Hinterberger, Timothy J. (2010)
The muscle regulatory factor MRF4 is expressed in both embryonic and adult vertebrate skeletal muscle cells. In mammals the MRF4 gene has a complex cis-regulatory structure, with many kilobases (kb) of upstream sequence required for embryonic expression in transgenic mice. Here, initial functional comparison between Xenopus and mammalian MRF4 genes revealed that 610 base pairs (bp) of the XMRF4a proximal promoter drove substantial transgenic expression in X. laevis myogenic cells, from somites of neurula embryos through adult myofibers, and as little as 180 bp gave detectable expression. Over 300 bp of XMRF4a proximal promoter sequence is highly conserved among three X. laevis and X. tropicalis MRF4 genes, but only about 150 bp shows significant identity to mammalian MRF4 genes. This most-conserved XMRF4a region contains a putative MEF2 binding site essential for expression both in transgenic embryos and in transfected mouse muscle cells. A rat MRF4 minimal promoter including the conserved region also was active in transgenic X. laevis embryos, demonstrating a striking difference between the mouse and Xenopus transgenic systems. The longest XMRF4a promoter construct tested, with 9.5 kb of 5′-flanking sequence, produced significantly greater expression in transfected mouse cells than did promoters 4.3-kb or shorter, suggesting that the intervening region contains an enhancer, although no increased expression was evident when this region was included in transgenic X. laevis embryos. Further identification and analysis of Xenopus MRF4 transcriptional control elements will offer insights into the evolution of this gene and of the myogenic gene regulatory network.